22nd Digital Avionics Systems Conference. Proceedings (Cat. No.03CH37449)
DOI: 10.1109/micro.2003.1253197
|View full text |Cite
|
Sign up to set email alerts
|

Comparing program phase detection techniques

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
5

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 25 publications
1
122
0
5
Order By: Relevance
“…Balasubramonian et al [19] used cache miss rates, cycles per instruction (CPI), and branch frequency characteristics to detect changes in application characteristics for cache tuning, and found that these characteristics were effective for phase classification. Dhodapkar et al [20] found a relationship between phases and the phases' working sets, and concluded that phase changes could be detected by detecting changes in the working set. In this work, we use execution statistics obtained from the microprocessor's hardware performance counters for phase classification [21].…”
Section: Phase-based Tuning and Dtmmentioning
confidence: 99%
See 1 more Smart Citation
“…Balasubramonian et al [19] used cache miss rates, cycles per instruction (CPI), and branch frequency characteristics to detect changes in application characteristics for cache tuning, and found that these characteristics were effective for phase classification. Dhodapkar et al [20] found a relationship between phases and the phases' working sets, and concluded that phase changes could be detected by detecting changes in the working set. In this work, we use execution statistics obtained from the microprocessor's hardware performance counters for phase classification [21].…”
Section: Phase-based Tuning and Dtmmentioning
confidence: 99%
“…For each generation, TaPT uses the previous generation's Pareto optimal set as the current generation's initial archive (line 15). TaPT calculates the fitness of the configurations in each population and archive using Equations (2) and (3), and updates the current generation's archive with the non-dominated configurations (lines [17][18][19][20][21]. To maintain the size of P i 's archive at A size , TaPT discards the least fit configurations or adds the most fit configurations from the population (line 22).…”
Section: Tapt Characterization Algorithmmentioning
confidence: 99%
“…It examines the application's execution path to detect hardware independent phases [21,14]. Such phases can be readily missed by performance counter based phase detection, while changes in executed code reflect changes in many different metrics [20,21,5,22,9,18]. To leverage this, ScarPhase monitors what code is executed by dividing the application into windows and using hardware performance counters to sample which branches execute in a window.…”
Section: Phase Detectionmentioning
confidence: 99%
“…where c new_est is the new estimate, c est is the old estimate, BW est is the estimated bandwidth demand, BW m is the measured bandwidth received and finally, BW M AX is the maximum bandwidth our system can provide 5 . In other 5 We estimated the real-world bandwidth limit of our reference system to approximately 12 GB/s using the STREAM benchmark [13].…”
Section: Bandwidthmentioning
confidence: 99%
See 1 more Smart Citation